Antibacterial Activity of Tobacco Flower Extract Against Staphylococcus Aureus and Pseudomonas Aeruginosa - Puspawan Hariadi; Andhini Yasmina Hukmi; Baiq Maylinda Gemantari (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Tobacco is known contains secondary metabolites such as flavonoids, alkaloids, and phenolic compounds which has pharmacological activity. As a part of the plant, it flowers have not been widely explored but are potentially rich in bioactive compounds that may be utilized as natural antibacterial agents. Aim: this study aimed to determine the antibacterial potential of tobacco flower extract against Gram-positive and Gram-negative bacteria. Methods: The ethanolic extract of tobacco flowers was obtained using a graded maceration method. The experimental groups were divided into six groups, consisting of four treatment groups with extract concentrations of 20%, 30%, 40%, and 50%, as well as one positive control group and one negative control group. Antibacterial activity was evaluated using the disc diffusion method. Result: The results showed that tobacco flower extract at concentrations at 20%, 30%, 40%, and 50% revealed inhibition zone diameters against Staphylococcus aureus as 0.6 mm, 1.5 mm, 1.8 mm, and 3 mm respectively, while were 0.5 mm, 0.6 mm, 0.6 mm, and 2.8 mm, respectively against Pseudomonas aeruginosa the inhibition zones. The positive control exhibited inhibition zone diameters of 18.6 mm against Staphylococcus aureus and 15.8 mm against Pseudomonas aeruginosa, whereas the negative control showed no inhibition zone (0 mm) against both test bacteria. Those activities known related to secondary metabolites compound that could inhibit bacterial growth. Conclusion: Based on those findings, the potency of tobacco flower extract posses inferior in antibacterial activity.